Peran Sumber Daya Manusia Dalam Struktur Lembaga Organisasi: Laporan Hasil Kuliah Kerja Lapangan di DHD Bpk Angkatan 45 Jawa Timur - Adhiyaksa Rahman Buwana; I Gede Wiyasa (Universitas 45 Surabaya, 2025)
The Generation of 45 Institution was established by the President of the Republic of Indonesia with Presidential Decree of the Republic of Indonesia Number 50 of 1984 as an institution engaged in the field of moral strength in order to continue to preserve the Spirit and Values ​​of the Struggle of 45 to the younger generation of the nation's successors in filling development after the Proclamation of Independence of the Republic of Indonesia on August 17, 1945. The Regional Daily Council of the Generation of 45 of East Java Province as the Generation of 45 Organization in the framework of its main task of preserving the spirit, Spirit of Values ​​​​of 45 to the components of the younger generation filling independence, has a desire to remind all components of the young generation of the nation as the next generation who will continue development in filling the independence of the Republic of Indonesia to understand the history and culture of their nation by continuing to preserve the values ​​​​of the struggle of the Indonesian nation which at that time was ready to sacrifice body and soul for the realization of an independent, united, just and prosperous Indonesian state as the national ideals of the Indonesian nation are stated in the Preamble to the Constitution of the Republic of Indonesia. The Generation of 45 Organization as an organization engaged in the field of Moral Force has an obligation and cares to continue to maintain the Unitary State of the Republic of Indonesia.